Secretion of Dopa in Phaeochromocytoma - Louis, William J. (1972)
In a series of 11 cases with phaeochromocytoma, two patients were found in whom the tumour secreted dopa in addition to dopamine, noradrenaline, and adrenaline. These two patients were normotensive in spite of high plasma and urinary levels of noradrenaline and adrenaline. This raises the possibility that dopa may be able to protect against the hypertensive action of noradrenaline. Such a mechanism would also explain the absence of hypertension in many cases of neuroblastoma.